Treatment of water of swimming pools and baths. Part 1, General requirements : english traslation of DIN 19643-1:2023-06 = Aufbereitung von Schwimm- und Badebeckenwasser. Teil 1, Allgemeine Anforderungen : Englische Übersetzung von DIN 19643-1:2023-06 = Traitement de l'eau des bassins des bassins et des bains. Partie 1, Conditions générales : traduction anglaise de DIN 19643-1:2023-06 (Beuth Verlag, 2023)
International guidelines that focus on the quality and purification of swimming pool and bath water. Intended for professional public.
Keywords: hygiena; technika; koupele; Quality Control; Baths; Swimming Pools; Water Quality; řízení kvality; kvalita vody; čištění vody; plavecké bazény; environmentální vědy; Water Purification